PENDEKATAN METODE ALTMAN Z-SCORE DALAM PENENTUAN INSENTIF BONUS PEGAWAI - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2018)
Human resource management is one area of management that specifically studies the relationships and the role of humans in the organization. Human resource management can also produce a good performance in a company by way of valuation, reward service in each individual member organization in accordance with its work ability. Revenue earned by each individual will be different, including bonuses or incentives that are very useful to improve work motivation. Incentives given to each employee certainly not the same from one to another. This incentive calculation process requires the index as a factor factor in its final outcome. One method that can be used in the determination of the index is by using the Altman Z-Score method. This method can be used for determining the value used for the determination of bonus incentives.